Zolpidem for the Treatment of Dystonia - Badillo, Stephanie Patricia J.; Jamora, Roland Dominic G. (Frontiers in Neurology, 2019)
Background and Purpose: There are recent reports of zolpidem being effective for the treatment of a variety of movement disorders, due to its action on the gamma-aminobutyric acid A receptors in the thalamus, subthalamic nucleus and globus pallidus, hence facilitating inhibitory pathways in the basal ganglia motor loop. Its beneficial effects have been described for Parkinson’s disease and other related disorders. The objective of this study was to assess the therapeutic effects of zolpidem for various types of dystonia. Methods: We conducted a literature search using MEDLINE via PubMed, Cochrane Library, EMBASE, Scopus and Google Scholar. Results: There were no randomized controlled trials. The literature included 6 case reports, 4 case series and 1 non-randomized, non-controlled interventional trial. Overall, 49 adult participants (range 1-34 participants) with a mean age of 49.5 years were treated. Regardless of the dystonia subtype, a single dose of zolpidem at 10 mg causes improvement of symptoms for a mean duration of 3.4 hours until patient returns to baseline. The main adverse effect noted was drowsiness, which was dose-dependent. Conclusion: While the current available literature suggests that zolpidem may be an effective pharmacologic option for treating dystonia, however the quality of evidence remains limited. Larger sample size, methodological consistency and randomized controlled trials with long-term patient follow-ups are necessary to come up with definitive conclusion.